The Mapuche Palin as a teachable bodily practice in Chilean physical education: reflections for critical thinking in education (Agora for Physical Education and Sport, 2021)
This article puts in tension two educational sociocultural realities that frame Chilean education. On the one hand, the recognition that everything Chilean is impregnated with an uprooting of the Mapuche on the basis of a whitewashed and racist construction of the conformation of Chilean society and, on the other hand, what distinguishes the history of physical education in this country, the tribute to the hegemony of Eurocentric knowledge. Both aspects come to reveal the contradictions and limitations of the circulation of an ancestral knowledge such as the physical practice of the palin in physical education classes.
Keywords: Mapuche; palin; critical thinking; education